2017
DOI: 10.1155/2017/3953248
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Intraventricular Hemorrhage following a Ventriculoperitoneal Shunt Placement: Exploring the Surgical Anatomy of a Rare Complication

Abstract: Ventriculoperitoneal shunt (VPS) placement is one of the commoner neurosurgical procedures worldwide. The purpose of this article is to report a case of delayed intraventricular hemorrhage (IVH) following a VPS and to review the literature regarding anatomic factors that could potentially explain this rare complication. A 78-year-old man with normal pressure hydrocephalus, who underwent an uneventful right VPS placement, suffered from a catastrophic isolated IVH five days later. The reported cases of delayed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…An EVD and VP shunts are inserted using the same frontal approach, which is an invasive brain procedure that may cause neural injury in patients[ 21 ]. Some authors have proposed that catheter insertion may lead to a disturbance in venous return or hemostasis of a cortical vein and then contribute to subcortical hemorrhage[ 15 , 17 , 22 ]. Brain edema around the catheter is regarded as a radiographic sign of vascular erosion and could be used to predict DICH.…”
Section: Discussionmentioning
confidence: 99%
“…An EVD and VP shunts are inserted using the same frontal approach, which is an invasive brain procedure that may cause neural injury in patients[ 21 ]. Some authors have proposed that catheter insertion may lead to a disturbance in venous return or hemostasis of a cortical vein and then contribute to subcortical hemorrhage[ 15 , 17 , 22 ]. Brain edema around the catheter is regarded as a radiographic sign of vascular erosion and could be used to predict DICH.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the DICH secondary to VP shunt are still controversial. Several hypotheses have been proposed: (1) erosion of cerebral vasculature by the insertion of catheter; (2) fragility of cerebral tissue caused by advanced age, craniotomy, trauma or stroke; (3) disseminated intravascular coagulation (DIC) induced by VP shunt; (4) coagulopathy, anticoagulant or antiplatelet therapy; (5) sudden change of intracranial pressure after manipulation of the valve system 7 , 19 . Savitz and Bobroff 5 pointed out that the mechanism of DICH was more likely erosion of surface or deeper small vessel by catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Mild hemorrhage is frequently observed in the ventricle or in the parenchyma soon after operation 5 , and the rate could be up to 43.1% 6 . However, the delayed intracerebral hemorrhage (DICH) is considered to be a rare but potentially severe event 7 , the mortality is as high as 50% 4 . The risk factors and underlying mechanisms of DICH are still not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed intracranial hemorrhage at the site of catheter placement is an uncommon-but-severe complication of ventriculoperitoneal shunt placement and is associated with predisposing factors, including degenerative vascular change and puncture of the choroid plexus. 29 Similarly, intracranial hemorrhage and intraventricular hemorrhage have long been documented as potential complications of shunt removal and are commonly attributed to the disruption of the choroid plexus that has grown around and into the catheter. [30][31][32][33] A retrospective review of 35 pediatric patients with a total of 52 shunt revisions found that 25% of the revisions resulted in intraventricular hemorrhage, though only 2% of such revisions were deemed clinically relevant, resulting in .5 mL of blood.…”
Section: Discussionmentioning
confidence: 99%